Boat Representation in Nusantara Architecture - Vini Asfarilla; Yulianto P. Prihatmaji (Talenta Publisher, 2019)
Architecture is one of the arts of cultural product, archipelago culture rooted in traditional culture, vice versa. Traditional architecture is very diverse in Indonesia, along with the diversity of its ethnic. Traditional architecture is building with form and function which has its own characteristic, inherited from generation to generation that can be used to hold activity by the people around it. Therefore, traditional architecture is the cultural expression and direct reflection in presenting something by its people. Some Nusantara Architectures adopt boat as the representation for building’s form. Therefore, the author is interested to prove the correlation of boat as representation in some archipelago architectures. This research uses data search method through literature studies by collecting data on some researched archipelago architecture buildings' form and construction system. From these data, a correlation between boat form representation and construction system used in boats and buildings can be concluded. Keyword: Nusantara Architecture, Form of Architecture, Boat Construction, Boat Representation.